Single Higgs-boson production at a photon-photon collider: general 2HDM versus MSSM - López-Val, David; Solà Peracaula, Joan (Physics letters, 2011)
We revisit the production of a single Higgs boson from direct γγ-scattering at a photon collider. We compute the total cross-section σ(γγ→h) (for h=h0,H0,A0), and the strength of the effective gh0γγ coupling normalized to the Standard Model (SM), for both the general Two-Higgs-Doublet Model (2HDM) and the Minimal Supersymmetric Standard Model (MSSM). In both cases the predicted production rates for the CP-even (odd) states render up to 104 (103) events per 500 fb−1 of integrated luminosity, in full consistency with all the theoretical and phenomenological constraints. Depending on the channel the maximum rates can be larger or smaller than the SM expectations, but in most of the parameter space they should be well measurable. We analyze how these departures depend on the dynamics underlying each of the models, supersymmetric and non-supersymmetric, and highlight the possible distinctive phenomenological signatures. We demonstrate that this process could be extremely useful to discern non-supersymmetric Higgs bosons from supersymmetric ones. Furthermore, in the MSSM case, we show that γγ-physics could decisively help to overcome the serious impasse afflicting Higgs boson physics at the infamous “LHC wedge”.